CAUSALITY OF DEFINITIONS "COMPETITIVE COMPETITIVENESS" AND "COMPETITIVENESS OF INNOVATIONS": EPISTEMOLOGICAL ANALYSIS FROM THE POSITION OF MANAGEMENT GOALS (Development Service Industry Management, 2024)
The purpose of the article is to prove the causality of the definitions of "enterprise competitiveness" and "innovation competitiveness" from the point of view of management goals and justify the feasibility of using the definition "innovation competitiveness" and its modifications in the terminological dictionary of the theory of innovation. When studying the epistemology of the term "enterprise competitiveness", we took into account a common feature in the set of definitions chosen for analysis - the relative nature of competitiveness as an object of management, and therefore, the relative nature of the methods of evaluating comparative criteria, which can affect the perception by target consumers of the degree of usefulness embedded in the innovation. Taking into account the high variability of the business environment and the structure of consumer needs, the expediency of using a value-oriented approach to managing the competitiveness of innovations is argued. In line with this approach, the author's position is expressed regarding the need to introduce the definition of "competitiveness of innovation", considering it in the context of comparing the alternatives of the final version of the implemented changes, which have undergone the entire set of works to create value and act as a means of satisfying a certain consumer need. Taking this into account, the features distinguishing internal and external innovations are highlighted. The internal "competitiveness of innovations" is proposed to be considered as the best option for innovative changes in the internal environment of the enterprise according to the established parameters, aimed at solving the problem that worsened/deteriorated its competitiveness in the strategic area of ​​management. External - as a better way to meet consumer needs, which tends to increase in demand by target audiences. It is emphasized that in both cases it makes it possible to determine the potential of utility (value) embedded in the innovation and to form a criterion base for comparative evaluation of consumer value compared to competitors.
Keywords: consumer value of the product offer; target audiences; internal competitiveness of innovations; external competitiveness of innovations; competitive advantages